Virtue in Plato's Republic and Machiavelli's Prince - Masís Iverson, Katherine (2014)
From a virtue ethics point of view, this paper compares Plato’s philosopher-kings with Machiavelli’s prince. First, virtue ethics is defined, next, the way in which virtue manifests in Plato’s Republic and Machiavelli’s Prince is explained. Finally, similarities and differences with respect to virtue ethics between both authors are assessed.